2017
DOI: 10.1093/mnras/stx1014
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the non-linear clustering of high-redshift galaxies

Abstract: We incorporate the non-linear clustering of dark matter halos, as modelled by Jose et al. (2016) into the halo model to better understand the clustering of Lyman break galaxies (LBGs) in the redshift range z = 3 − 5. We find that, with this change, the predicted LBG clustering increases significantly on quasi-linear scales (0.1 ≤ r / h −1 Mpc ≤ 10) compared to that in the linear halo bias model. This in turn results in an increase in the clustering of LBGs by an order of magnitude on angular scales 5 ≤ θ ≤ 100… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 61 publications
1
19
0
Order By: Relevance
“…We perform a power law fit to the large scale clustering from scales of 1 Mpc/h to 100 Mpc/h and look for deviations from power-law at smaller scales (r < 1 Mpc/h). We note that the powerlaw behavior prevails all the way to (r < 0.1 Mpc/h), which is a direct consequence of the non-linear halo bias in the two-halo regime (Jose et al 2017(Jose et al , 2016;BlueTides clustering confirms that non-linear bias is indeed required to model clustering at quasilinear scales (0.5 − 10Mpc/h) as seen in Figure 5 of our earlier paper (Bhowmick et al 2018). In the one-halo regime (r < 0.1 Mpc/h), simulations predict enhancement (by factors of upto ∼ 10) compared to power law.…”
Section: Total Clustering: How Close Is It To Power Law?supporting
confidence: 72%
“…We perform a power law fit to the large scale clustering from scales of 1 Mpc/h to 100 Mpc/h and look for deviations from power-law at smaller scales (r < 1 Mpc/h). We note that the powerlaw behavior prevails all the way to (r < 0.1 Mpc/h), which is a direct consequence of the non-linear halo bias in the two-halo regime (Jose et al 2017(Jose et al , 2016;BlueTides clustering confirms that non-linear bias is indeed required to model clustering at quasilinear scales (0.5 − 10Mpc/h) as seen in Figure 5 of our earlier paper (Bhowmick et al 2018). In the one-halo regime (r < 0.1 Mpc/h), simulations predict enhancement (by factors of upto ∼ 10) compared to power law.…”
Section: Total Clustering: How Close Is It To Power Law?supporting
confidence: 72%
“…The value δ=0.8 has been found to be appropriate for both observations and theories at the physical separation of ;0.1-10 h −1 Mpc (e.g., Peebles 1980;Davis & Peebles 1983;Zehavi et al 2005;Coil et al 2007Coil et al , 2008. This statement still holds for the galaxy samples at redshift up to ;5 (δ=0.8-1.1; Ouchi et al 2005;Coil et al 2006;Kashikawa et al 2006;Lee et al 2006;Hildebrandt et al 2009;Durkalec et al 2015;Harikane et al 2016;Jose et al 2017). Measurement of ω(θ) could be biased, since our sample is located in a single, area-limited region that may not be representative of the true underlying mean density over the whole sky.…”
Section: Two-point Autocorrelation Functionmentioning
confidence: 72%
“…These non-linear effects are very often not taken into account in analytical models for the two-halo correlation, although very recent studies have started incorporating the scale dependence in the twohalo regime (Harikane et al 2017;Jose et al 2017) into clustering analysis of observed galaxies and found that accounting for non-linear halo bias can significantly affect the estimates of galaxy bias and halo masses. One must note that most of the previous works are based on N-body simulations, whereas BLUETIDES is a high resolution hydrodynamic simulation (includes baryons) which can directly probe the non-linear clustering properties of galaxies; in our next paper (Bhowmick et.…”
Section: Discussionmentioning
confidence: 99%